DOI: 10.18297/etd/2085
|View full text |Cite
|
Sign up to set email alerts
|

The impact of participation in a first-year seminar on increased usage of campus resources, academic and social integration and first-to-second-semester persistence at a two-year community and technical college.

Abstract: Lafferty, Kaye 1964-, "The impact of participation in a first-year seminar on increased usage of campus resources, academic and social integration and first-to-second-semester persistence at a two-year community and technical college." (2015). Eric, you are truly the APA king and I will be forever grateful to you for all your writing and editing advice.I will be forever thankful for Dr. Suzette Scheuermann's positive optimism and passion, insightful discussions, and suggestions. Her enthusiasm is truly contagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 100 publications
(213 reference statements)
2
1
0
Order By: Relevance
“…However, the utilization frequency of campus resources did not reveal any significant differences between the two groups, which appeared to be related to the number of credit hours completed by each group, as the C group hours were significantly higher than the S group's. The impact of the first-year seminar on student awareness was consistent with most previous research, except in terms of the utilization frequency of campus resources, which was not consistent with Yale (2000) or Lafferty (2015).…”
Section: Discussion and Conclusion Discussion Of Study Findingssupporting
confidence: 73%
See 2 more Smart Citations
“…However, the utilization frequency of campus resources did not reveal any significant differences between the two groups, which appeared to be related to the number of credit hours completed by each group, as the C group hours were significantly higher than the S group's. The impact of the first-year seminar on student awareness was consistent with most previous research, except in terms of the utilization frequency of campus resources, which was not consistent with Yale (2000) or Lafferty (2015).…”
Section: Discussion and Conclusion Discussion Of Study Findingssupporting
confidence: 73%
“…The third part of this study explored the effect of the seminar on general attitudes toward university education in three sectionsgeneral satisfaction, commitment and capability to finish college, and citizenship responsibility behavior. It was found that the seminar had a clear positive influence on student perceptions of education quality, and more S group students expressed a greater commitment to continuing their studies at this university, as well as greater awareness of how to develop their own leadership skills using the available training opportunities; however, there was no clear significant difference between the two groups in terms of citizenship responsibility behavior, all of which were in line with the results in Sanchez et al (2006), the National Survey of Student Engagement (2005), and Lafferty (2015), but were contrary to Hendel (2007), which found no impact on overall satisfaction for first-year seminar students. Overall, the results showed that the first-year seminar significantly increased positive attitudes toward the college.…”
Section: General Attitudes Toward Higher Educationsupporting
confidence: 74%
See 1 more Smart Citation